Direct evidence from STXM analysis of enhanced oxygen storage capacity in ceria through the addition of Cu and Mg: Correlation of HT-WGS reaction performance - Lee, Ru Ri; Kim, Dong Hyun; Jeon, Kyung Won; Jeon, I. Jeong; Kim, Chang Hyeon; Ditter, Alexander S.; Shapiro, David A.; Marcus, Matthew A.; Ohldag, Hendrik; Bustillo, Karen C.; Yu, Young sang; Jang, Won Jun; et al. (Chemical Engineering Journal, 2024)
Here, scanning transmission X-ray microscopy (STXM) analysis was utilized to directly present visual evidence of changes in oxygen storage capacity (OSC) when small amounts of an additive were incorporated into CeO2. Specifically, the chemical map measured by STXM analysis differentiated between Cu-rich and Ce-rich areas to derive the proportion of Ce3+. Additionally, we found that the dispersion of Cu significantly influenced the formation of OSC. The findings were applied to the high-temperature water–gas shift reaction for producing high-purity hydrogen from waste-derived syngas, establishing a correlation with catalyst performance. Consequently, the CCM75 (Ce/Mg = 75/25) catalyst demonstrated the highest Cu dispersion and OSC values (6.9 %, 800.3 μmolO/gcat), and it also showed the highest CO conversion (79 % at 450 °C) and stability (−7.7 % at 450 °C after 50 h), attributed to the significant presence of active Cu. This study confirms previously reported interactions between Cu and CeO2 and uncovers the significant roles of Cu and Mg in this catalysis system, providing new understanding of the mechanisms that facilitate OSC improvement.
Keywords: Catalytic performance; Ce 3+; Chemical maps; Oxygen storage capacity; Reaction performance; Scanning transmission X-ray microscopy; Transmission X-ray microscopies; Visual evidence; WGS reactions; Catalytic performance; Chemical map; Oxygen storage capacity (OSC); STXM